Design of a UHF Antenna for Partial Discharge Detection of Power Equipment. (15th October 2014) - Wang, Youyuan; Wu, Junfeng; Chen, Weigen; Wang, Yajun
Abstract : A single-arm Archimedean spiral antenna that can be directly fed by a 50 Ω coaxial cable is investigated in this study. Every antenna parameter is optimized under simulation to make the antenna work in the ultra-high frequency band. The influence of dielectric materials, feed cone angle, and antenna duty ratio is also examined. Partial discharge (PD) experiments on several typical artificial insulation defects are conducted, and a single-arm Archimedean spiral antenna and a typical microstrip antenna are utilized for PD measurement. The PD characteristics of different insulation defects are also analyzed. Results show that the designed antenna is suitable for ultra-high frequency monitoring. The detection sensitivity of the single-arm spiral antenna is superior to that of the ordinary microstrip antenna. The former can be utilized in wide-band measurement fields.